Dipeptides as environmentally friendly CH4 hydrate inhibitors: Experimental and computational approaches. (1st December 2022) - Go, Woojin; Yun, Soyeong; Lee, Dongyoung; Seo, Yongwon
Graphical abstract: Highlights: Dipeptides (Ala-Ala, Ala-Gly, and Gly-Gly) were proposed as effective CH4 hydrate inhibitors. Hydrate onset temperatures were measured using an HP autoclave and an HP μ-DSC. MD simulations were conducted to reveal the inhibition mechanism of the dipeptides. The N -termini of the dipeptides were found essential for CH4 hydrate inhibition. Abstract: In this study, three dipeptides (Gly-Gly, Ala-Ala, and Ala-Gly) were appraised as environmentally benign hydrate inhibitors for CH4 hydrate using both experimental and computational methods. Their kinetic inhibition performance was experimentally evaluated using a stirred high-pressure autoclave and a non-stirred high-pressure micro-differential scanning calorimeter. The experimental results demonstrated that the three dipeptides functioned well as CH4 hydrate inhibitors. Ala-Gly was found to be the most effective, and its inhibition performance was comparable to that of polyvinylcaprolactam (PVCap), a polymer-based commercial hydrate inhibitor. Snapshots, hydrate counts, F3 and F4 order parameters, displacement magnitude, mean square displacement, and radial distribution functions of each peptide-containing system were examined using molecular dynamics (MD) simulations to reveal the inhibition mechanism of dipeptides. The MD simulations showed that the N -termini of the dipeptides were the key constituents for inhibiting the CH4 hydrate, and the Ala-Gly-containing system had the strongest interaction between dipeptide molecules and CH4 hydrate. The overall results provide a better understanding of nature-derived, environmentally friendly hydrate inhibitors and offer insights into the molecular inhibition mechanism of various potential inhibitors.